8z-12=3(3z+11)-z

Simple and best practice solution for 8z-12=3(3z+11)-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z-12=3(3z+11)-z equation:



8z-12=3(3z+11)-z
We move all terms to the left:
8z-12-(3(3z+11)-z)=0
We calculate terms in parentheses: -(3(3z+11)-z), so:
3(3z+11)-z
We add all the numbers together, and all the variables
-1z+3(3z+11)
We multiply parentheses
-1z+9z+33
We add all the numbers together, and all the variables
8z+33
Back to the equation:
-(8z+33)
We get rid of parentheses
8z-8z-33-12=0
We add all the numbers together, and all the variables
-45!=0
There is no solution for this equation

You can always share this solution

See similar equations:

| 14y-4y+4y-12y=6 | | 4×-3y=44 | | 1/3(3x-9)=10 | | 1/3(3x-99)=10 | | 729=x*x*x | | 3a+7a=32 | | x*0.25=0.2 | | 48.98/82.88=x | | 3c-18=2 | | 5/6*z=15/42 | | x÷21=13 | | 0+33y=-6 | | 4^2x3^=0 | | –x–2=-1/3x+2 | | 3y+14=11y–1 | | 12-6x=1+2x/3 | | K^2-6k+20=0 | | x+0.02x=1528 | | 4y-7+2y=5y-6+19 | | 5x–4=3(x–1) | | 4n/15=12/5 | | 3/5=n/7 | | 3x-4=2.3 | | 3x=48-8 | | 3a^2+4a-5=0 | | 8t+6=5t+15 | | 2x-1=-1+3x | | 0.4n-0.4=12÷10 | | X+3=11(2x-15 | | y=4+2+10?5 | | 7(x-8)=3(x-14) | | 5y-19=4y+15 |

Equations solver categories